Audiovestibular Evaluation in Post COVID-19 Patients Discharged From Mansoura University Isolation Hospital: A Prospective Study - Abd Elmonem Elgarhy, Somaya Elsayed Elsayed; Abd-Eltawab, Mohamed Mostafa; Morgan, Ashraf Elsayed; Elhadidy, Tamer Ali; El-Sharabasy, Ayman El-Saeed (Journal of Neonatal Surgery, 2025)
Background: While COVID-19 is primarily a respiratory illness, emerging evidence suggests it may have neurotropic properties, including potential impacts on the auditory and vestibular systems. Early symptoms such as fever, cough, and fatigue were well-documented, but reports of anosmia and balance disturbances raised concerns regarding broader neurological involvement. Objective: This study aimed to assess the audiovestibular function in post-COVID-19 patients and to characterize the potential subclinical and clinical effects of SARS-CoV-2 on the auditory and balance pathways. Methods: A total of 130 post-COVID-19 patients (mean age: 38.64 ± 10.03 years; 70.8% female) were evaluated 1–3 months after confirmed recovery. Audiological assessments included pure tone audiometry (PTA), distortion product and transient evoked otoacoustic emissions (DPOAE and TEOAE), and auditory brainstem response (ABR). Vestibular evaluation included spontaneous and positional nystagmus testing and caloric tests. Results: Audiovestibular symptoms were reported as dizziness (72.3%), tinnitus (12.3%), and hearing loss (8.5%). PTA revealed elevated thresholds particularly at high frequencies, while DPOAE and TEOAE amplitudes were reduced in a substantial portion of cases, especially among older individuals and males. ABR testing showed no significant alterations, though a subset exhibited absent waveforms. Vestibular testing identified benign paroxysmal positional vertigo (BPPV) and peripheral vestibular lesions in a notable proportion of patients. Age was significantly associated with both hearing loss and OAEs outcomes (P < 0.001), while gender differences were also observed in DPOAE and TEOAE results. Conclusion: These findings support the hypothesis that SARS-CoV-2 may affect cochlear outer hair cells and vestibular function, even in the absence of overt auditory symptoms. The observed dysfunction appears to be more prominent with increasing age but shows no correlation with the time elapsed since infection. Early audiovestibular assessment may be warranted following COVID-19 infection, and longitudinal studies are needed to better understand the persistence and pathophysiology of these effect.